2020
DOI: 10.7554/elife.47946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helical kink in antimicrobial peptides on membrane pore formation

Abstract: Every cell is protected by a semipermeable membrane. Peptides with the right properties, for example Antimicrobial peptides (AMPs), can disrupt this protective barrier by formation of leaky pores. Unfortunately, matching peptide properties with their ability to selectively form pores in bacterial membranes remains elusive. In particular, the proline/glycine kink in helical peptides was reported to both increase and decrease antimicrobial activity. We used computer simulations and fluorescence experiments to sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 100 publications
3
68
1
Order By: Relevance
“…For example, studies of pardaxin in the membrane have demonstrated the importance of cationic residues and phenylalanine residues on peptide association with lipids [806]. Finally, MD simulations allow for the study of the effect of chemical modification on the peptides (e.g., amidation) [787] and the effect of helical kink on peptide insertion into the bilayer [816,817].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…For example, studies of pardaxin in the membrane have demonstrated the importance of cationic residues and phenylalanine residues on peptide association with lipids [806]. Finally, MD simulations allow for the study of the effect of chemical modification on the peptides (e.g., amidation) [787] and the effect of helical kink on peptide insertion into the bilayer [816,817].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…Homology analysis and functional prediction used the BLAST programme and UniProt database, which showed that this peptide belonged to the brevinin-1 family, which has multiple potential functions. Like other brevinin-1 peptides ( Figure 1 B), in addition to having the distinctive feature of a rana box, B1OS had the highly conserved residues of Ala9, which tended to contribute to helix formation [ 19 ], and Pro14, which induced a stable kink facilitating toroidal pore formation in bacterial membranes [ 20 ]. Interestingly, by alignment comparison, it was found that an FLP motif at the N-terminus was highly conserved in most brevinin-1 family members, whereas a hydrophobic leucine residue was lacking at the second position of B1OS and brevinin-1HSb.…”
Section: Discussionmentioning
confidence: 99%
“…The glycine-proline hinge region was added to the mutant peptides, considering that almost all cecropin and cecropin-like peptides contain the alanine glycine-proline region [ 31 ]. The glycine-proline hinge region in the middle of the helical structure can benefit the pore-forming peptides [ 40 ]. Conversely, another study about cecropin attempting to delete the proline-glycine hinge resulted in decreasing antimicrobial activity, although there was an increase in anti-inflammatory activity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result was in line with the estimate that most helicity improvements usually increase the activity of peptides [ 46 ]. It was suspected that the addition of the glycine-proline hinge region increased the overall helicity value of the peptides [ 40 ]. Despite, the insertion of proline might be interrupted the helical span [ 47 ], the deletion of negative charge residues helped to conform an idealized amphipathic helix, with distinct hydrophobic and hydrophilic facets [ 22 ].…”
Section: Discussionmentioning
confidence: 99%